GROUPS OF COMPANIES IN INSOLVENCY PROCEEDINGS - ROMANIAN AND INTERNATIONAL PERSPECTIVE - Gabriela FIERBINŢEANU (Challenges of the Knowledge Society)
Insolvency proceedings in case of groups of companies is no longer a surprise but a reality that concerned in the last period of time the romanian and also the european lawmakers.Although at an intuitive level the understanding of this construction must not raise many questions it is proven that not always what you see is what you get, especially when insolvency proceedings are opened in case of groups of companies.The aim of this article is to offer a global image on the effort made on national and international level to codify and harmonize the insolvency law provisions in the field.